2017
DOI: 10.1001/jama.2016.19193
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Supplementation for the Prevention of Neural Tube Defects

Abstract: IMPORTANCENeural tube defects are among the most common congenital anomalies in the United States. Periconceptional folic acid supplementation is a primary care-relevant preventive intervention.OBJECTIVE To review the evidence on folic acid supplementation for preventing neural tube defects to inform the US Preventive Services Task Force for an updated Recommendation Statement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 41 publications
1
84
0
15
Order By: Relevance
“…Folic acid supplementation before pregnancy and just during postpartum period for at least four weeks helps to protect the occurrence of neural tube defects and other congenital abnormalities [811]. And having awareness about preconception folic acid supplementation is very important for women to start taking folic acid early.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Folic acid supplementation before pregnancy and just during postpartum period for at least four weeks helps to protect the occurrence of neural tube defects and other congenital abnormalities [811]. And having awareness about preconception folic acid supplementation is very important for women to start taking folic acid early.…”
Section: Discussionmentioning
confidence: 99%
“…According to different interventional studies done in different countries, administering of 0.4 mg of folic acid for the reproductive age group three months before pregnancy, during pregnancy period, and up to one month after pregnancy has been associated with up to 80% reduction in specific congenital anomalies including neural tube defects (NTDs) with associated hydrocephalus, oral facial clefts with or without cleft palate, congenital heart disease, urinary tract anomalies, and limb defects, as well as some pediatric cancers [411]. Many articles revealed that preconception folic acid supplementation is associated with increased fetal growth resulting in higher placental and birth weight, and decreased risks of low birth weight and small for gestational age [1214].…”
Section: Introductionmentioning
confidence: 99%
“…2 While in 2000, the FNB has set the RDA for folic acid for pregnant women at 360 mcg and the UL between 480–600 mcg per day, based on a systematic review a recent US Preventive Service Task Force (USPSTF) recommends that all women planning or capable of pregnancy take a daily supplement containing 400 to 800 mcg of folic acid. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The most common NTDs are spinal cord and spina bifida and anencephaly [8]. Folic acid supplementations for pregnant women are an effective primary care-relevant preventive intervention [9]. America and many other countries issued the regulations to require amending the standards of several grain products and vegetable by folic acid addition [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…America and many other countries issued the regulations to require amending the standards of several grain products and vegetable by folic acid addition [7,10,11]. As recommended, all women of childbearing age should take 400 to 800 micrograms folic acid per day during the periconceptional and pregnancy [9,[12][13][14][15][16]. Women who had a fetus diagnosed as affected by a neural tube defect or have given birth to a baby with a neural tube defect have an increased risk and should be administered high-dose supplementation (5 mg folic acid daily) [17].…”
Section: Introductionmentioning
confidence: 99%